2003
DOI: 10.1093/hmg/ddg283
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein degradation by serine protease neurosin: implication for pathogenesis of synucleinopathies

Abstract: Accumulation of insoluble alpha-synuclein aggregates in the brain is characteristic of Parkinson's disease, dementia with Lewy bodies and multiple system atrophy. Although numerous studies on the aggregation properties of alpha-synuclein have been reported, little is known about its degradation so far. In view of proteolytic degradation, we have found that the serine protease neurosin (kallikrein-6) degrades alpha-synuclein and co-localizes with pathological inclusions such as Lewy bodies and glial cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 41 publications
4
128
1
1
Order By: Relevance
“…This approach revealed that genes affected by disease but not gender were involved several cellular processes such as transmission of nerve impulse, synaptic transmission, cell-cell signaling, establishment of localization, localization, transport (Fig 3). Among the genes that exhibit gender-independent altered expression in PD are: neuronal beta-catenin, which has been implicated in Alzheimer disease and synaptic plasticity (Fuentealba et al, 2004;Goda, 2002); PAEL-R, a protein accumulated in Lewy bodies (Murakami et al, 2004) and a potential parkin substrate (Nakahara et al, 2003;Yang et al, 2003); kallikrein 6, involved in ASYN degradation (Iwata et al, 2003); and transferrin, which may be related to iron deposition observed in PD brain (Morris et al, 1994).…”
Section: Microarray Resultsmentioning
confidence: 99%
“…This approach revealed that genes affected by disease but not gender were involved several cellular processes such as transmission of nerve impulse, synaptic transmission, cell-cell signaling, establishment of localization, localization, transport (Fig 3). Among the genes that exhibit gender-independent altered expression in PD are: neuronal beta-catenin, which has been implicated in Alzheimer disease and synaptic plasticity (Fuentealba et al, 2004;Goda, 2002); PAEL-R, a protein accumulated in Lewy bodies (Murakami et al, 2004) and a potential parkin substrate (Nakahara et al, 2003;Yang et al, 2003); kallikrein 6, involved in ASYN degradation (Iwata et al, 2003); and transferrin, which may be related to iron deposition observed in PD brain (Morris et al, 1994).…”
Section: Microarray Resultsmentioning
confidence: 99%
“…Currently, the actual protease system(s) responsible for the cellular metabolism of ␣-Syn is unknown; however, a number of proteolytic systems are implicated in the cellular metabolism of ␣-Syn, including proteasomes (Bennett et al, 1999;Tofaris et al, 2001;Webb et al, 2003), lysosomes-autophagy (Paxinou et al, 2001;Webb et al, 2003), calpains (Mishizen-Eberz et al, 2003), and kallikrins (Iwata et al, 2003). Because aging is associated with decreases in the activity of these proteases (Goto et al, 2001;Gozal et al, 2003;Li et al, 2004), it is tempting to hypothesize that increases in the stability of ␣-Syn with aging could result from the decline in lysosomal and proteasomal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic clearance is possible using any of several proteases that have been identified to be able to cleave and degrade α-syn: these include neurosin, 55 matrix metalloproteinases (MMPs), 56 calpain, 57 cathepsin D 58 and plasmin. 59 Among them, neurosin, MMPs and plasmin have been reported to cleave and degrade extracellular α-syn.…”
Section: Other Clearance Systems As Therapeutic Approaches Against Pdmentioning
confidence: 99%
“…Neurosin, a serine protease, is preferentially expressed in neurons and oligodendrocytes in the brain. 55 It was first observed to be colocalized in some senile plaques in AD patients as well as Lewy bodies in PD patients. 60 It has also been reported to degrade intracellular α-syn, but less efficiently A53T α-syn and also to inhibit α-syn polymerization.…”
Section: Other Clearance Systems As Therapeutic Approaches Against Pdmentioning
confidence: 99%
See 1 more Smart Citation